The beginning of Czech scientific and journalistic interest in Belarusians, the Belarusian language and oral folk art - Kaleta, Petr (Journal of the Belarusian State University. History, 2023)
The author of the study analyses Czech research interest in Belarusian issues, especially from the first third of the 19th century to the beginning of 20th century. Pavel Jozef Šafárik can be considered the first personality to include Belarusian themes in his work. In the second half of the 19th century, professional interest was already growing and Belarusian topics appeared in Czech popular science periodicals. Czech researchers (I. J. Hanuš, K. J. Erben, P. Sobotka and J. H. Máchal) showed interest mainly in oral folk literature (national songs, mythologies, fairy tales or proverbs). The basic source for Czech researchers were the works of Russian and Polish authors. In the 1880s, two Czechs, motivated by their interest in Slavic issues, went directly to the territory of Belarusian gubernias, where they collected Belarusian national songs. One of them was the painter and collector of musical folklore Ludvík Kuba, the other was Slavist and researcher with considerable interest in Slavic folklore Adolf Černý, who even visited the Belarusian territory twice. It was Adolf Černý who became the central figure in Bohemia who, with the development of the Belarusian national movement at the beginning of the 20th century, wrote in the pages of Czech periodicals (mainly journals «Slavic Review» («Slovanský přehled») and «Time» («Čas»)) about all the national efforts of Belarusians at that time.
Keywords: Czechs; Belarusians; relations; publications; Belarusian language; Belarusian folklore; Adolf Černý